Acid aspiration-induced lung injury in rabbits is mediated by interleukin-8-dependent mechanisms. - Folkesson, H G (1995)
Acid aspiration lung injury may be mediated primarily by neutrophils recruited to the lung by acid-induced cytokines. We hypothesized that a major acid-induced cytokine was IL-8 and that a neutralizing anti-rabbit-IL-8 monoclonal antibody (ARIL8.2) would attenuate acid-induced lung injury in rabbits. Hydrochloric acid (pH = 1.5 in 1/3 normal saline) or 1/3 normal saline (4 ml/kg) was instilled into the lungs of ventilated, anesthetized rabbits. The rabbits were studied for 6 or 24 h. In acid-instilled rabbits without the anti-IL-8 monoclonal antibody, severe lung injury developed in the first 6 h; in the long-term experiments, all rabbits died with lung injury between 12 and 14 h. In acid-instilled rabbits given the anti-IL-8 monoclonal antibody (2 mg/kg, intravenously) either as pretreatment (5 min before the acid) or as treatment (1 h after the acid), acid-induced abnormalities in oxygenation and extravascular lung water were prevented and extravascular protein accumulation was reduced by 70%; in the long-term experiments, anti-IL-8 treatment similarly protected lung function throughout the 24-h period. The anti-IL-8 monoclonal antibody also significantly reduced air space neutrophil counts and IL-8 concentrations. This study establishes IL-8 as a critical cytokine for the development of acid-induced lung injury. Neutralization of IL-8 may provide the first useful therapy for this clinically important form of acute lung injury.